Overcoming the Not-in-My-Backyard Phenomenon in Waste Management: How Seoul Worked with a Citizens’ Opposition Movement and Built Incineration Facilities to Dispose of the City’s Waste, 1991–2013 - Han, Ahram (KDI School of Public Policy and Management, 2019)
Proper waste disposal is difficult, especially when no one wants disposal facilities in his or her neighborhood. A sound waste management plan has to consider both environmental sustainability and the wishes of the local community. In Seoul’s case, it took two decades of efforts to develop consensus on building and operating incinerators in the Republic of Korea’s capital city to dispose of residents’ waste. City officials held hundreds of open discussions to provide information on waste disposal and to listen to local residents’ concerns. Incorporating citizens’ demands, the government introduced stringent standards for pollutant emissions and related control systems, and it provided compensation to residents in the affected residential areas. At the same time that it built incinerators to dispose of the city’s trash, the government introduced new energy and recycling policies that made energy production more efficient and reduced waste generation. Those policies made residents’ heating and electricity bills more affordable and reduced the total amount of waste the city had to dispose of. Between 1991 and 2005, the city built four waste incineration facilities located in areas that collectively housed about 13,000 residents. The facilities operate harmoniously within those communities under the voluntary watch of residents. By 2013, the incinerators processed almost 80 percent of Seoul’s nonrecyclable municipal waste—a dramatic change compared with the late 1980s, when more than 90 percent of the city’s waste was dumped in a single landfill site.